PENGARUH KECANDUAN GAME ONLINE TERHADAP KEMAMPUAN MEMBACA SISWA KELAS V SDN 101779 PERCUT - Yurika Wihelmina; Eva Betty Simanjuntak; Laurensia Masri Perangin Angin; Edizal Hatmi; Natalia Silalahi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of online game addiction on the reading ability of fifth-grade students at SDN 101779 Percut. The research used a descriptive quantitative approach with a survey method. The sample consisted of 36 students from classes V-A and V-B. Data were collected through an online game addiction questionnaire and a reading ability observation test. The instruments were tested for validity and reliability, and the data were analyzed using normality test, linearity test, simple linear regression, Product Moment correlation, coefficient of determination, and hypothesis testing with IBM SPSS Statistics 32. The results showed that students’ online game addiction tended to be high, with 20 students or 55.55% classified in the high and very high categories. Meanwhile, students’ reading ability tended to be low, with 15 students or 41.66% classified in the low and very low categories. The regression equation was Y = 97.989 - 0.638X with a significance value of < 0.001. The correlation coefficient was r = -0.846, indicating a very strong negative relationship. The coefficient of determination was 0.716, meaning that online game addiction contributed 71.6% to students’ reading ability. Therefore, online game addiction has a negative and significant effect on students’ reading ability. This study aims to determine the effect of online game addiction on the reading ability of fifth-grade students at SDN 101779 Percut. The research used a descriptive quantitative approach with a survey method. The sample consisted of 36 students from classes V-A and V-B. Data were collected through an online game addiction questionnaire and a reading ability observation test. The instruments were tested for validity and reliability, and the data were analyzed using normality test, linearity test, simple linear regression, Product Moment correlation, coefficient of determination, and hypothesis testing with IBM SPSS Statistics 32. The results showed that students’ online game addiction tended to be high, with 20 students or 55.55% classified in the high and very high categories. Meanwhile, students’ reading ability tended to be low, with 15 students or 41.66% classified in the low and very low categories. The regression equation was Y = 97.989 - 0.638X with a significance value of < 0.001. The correlation coefficient was r = -0.846, indicating a very strong negative relationship. The coefficient of determination was 0.716, meaning that online game addiction contributed 71.6% to students’ reading ability. Therefore, online game addiction has a negative and significant effect on students’ reading ability.